Match performance and physiological capacity of female elite team handball players - Michalsik, L. B.; Madsen, K.; Aagaard, P. (International Journal of Sports Medicine, 2014)
The present study evaluated the physical demands imposed on female elite team handball players in relation to playing position. Female elite team handball field players were examined during match-play over a 5-year period using video based computerized locomotion analysis of tournament matches. In addition, physiological measurements during match-play and in separate physical tests were carried out. A total distance of 4 002±551 m (group means±SD) was covered per match with a total effective playing time of 50:42±5:50 min:s, while full-time players covered 4 693±333 m. On average, each player (n=83) performed 663.8±99.7 activity changes per match, and the mean speed was 5.31±0.33 km · h-1. High-intensity running constituted 0.8±0.5% of total effective playing time per match corresponding to 2.5±1.8% of the total distance covered. The amount of high-intensity running was reduced (p<0.05) 21.9% in the second half (44.9±16.8 m) compared to the first (57.5±21.3 m). Maximal oxygen uptake (VO2-max) was 3.49±0.37 l O2 · min-1 corresponding to 49.6±4.8 ml O2 · min-1 · kg-1. Mean relative workload during match-play was 79.4±6.4% of VO2-max. Mean total running distance in the Yo-Yo intermittent recovery test (level 1) was 1 436±222 m, which was greater in wing players (1 516±172 m, p<0.05) than pivots (1 360±118 m) and backcourt players (1 352±148 m). In conclusion, modern female elite team handball is a physically demanding intermittent team sport, where players are exposed to high relative workloads with substantial estimated aerobic energy expenditure interspersed by short periods of dominant anaerobic energy production as reflected by the limited amount of high-intensity running. Indications of fatigue and a resulting decline in physical performance were identified, since the amount of high-intensity running and the relative workload levels decreased in the second half. Positional differences were observed, with wing players covering a greater total distance than backcourt players, performing more high-intensity running and demonstrating a better intermittent recovery capacity (Yo-Yo test outcome) compared to both backcourt players and pivots.